2018
DOI: 10.3329/sja.v16i1.37419
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting extent of rural livelihood diversification in selected areas of Bangladesh

Abstract: The study was carried out to investigate the patterns and extent of livelihood diversification in rural Bangladesh. It also identified the major factors affecting extent of livelihood diversification. The study drew a random sample of 500 rural farm households in Bangladesh through a multi-stage sampling technique. The primary data were collected using semi-structured questionnaires, and analyzed using descriptive statistics and statistical techniques. The results showed that remittance contributed the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 8 publications
7
26
0
Order By: Relevance
“…This suggests that most of the households diversified their livelihoods into several options and earned higher amount of income from multiple livelihoods. Similar to these findings of Ahmed et al, (2018) who found high level of livelihoods diversification in rural Bangladesh as well as the findings of Verkaart et al, (2018) with evidence from Kenya.…”
Section: Income Generation From Farm and Off-farm Activitiessupporting
confidence: 85%
See 2 more Smart Citations
“…This suggests that most of the households diversified their livelihoods into several options and earned higher amount of income from multiple livelihoods. Similar to these findings of Ahmed et al, (2018) who found high level of livelihoods diversification in rural Bangladesh as well as the findings of Verkaart et al, (2018) with evidence from Kenya.…”
Section: Income Generation From Farm and Off-farm Activitiessupporting
confidence: 85%
“…The Simpsons Index of Diversity is generally expressed as; The value of SID ranges from zero (0) to one (1) such that zero (0) denotes specialization, the closer the value is to one, the more diversified the household and SID value of one (1) implies extreme diversification (Ahmed et al, 2018).…”
Section: Simpsons Index Of Diversity (Sid)mentioning
confidence: 99%
See 1 more Smart Citation
“…They identified the main occupations of the households of the rural people are mainly-Rice and non-rice crop, Petty business, Service or, Agricultural and non-agricultural laborer, remittance etc. The study also found that, remittance contributed highest share which accounts for 29% of the household's total income, followed by Petty business (20%) and rice crop (16%) [5].…”
Section: Basic Sample Characteristicsmentioning
confidence: 68%
“…In agriculture based economies like Bangladesh, this is often necessary where various types of risks are common which leads to low productivity, low output and invariably low income which continually trap the poor group in the vicious cycle of poverty. To avoid those risks in farming activity, households may shift to another non-farm or off farm activity which will provide them more income and less vulnerability [5]. For this reasons, Agriculture's share to rural household income dropped from about 60% in 1988 to 45% in 2008.…”
Section: Introductionmentioning
confidence: 99%